Bacteriophage targeting of gut bacterium attenuates alcoholic liver disease - Duan, Yi; Llorente, Cristina; Lang, Sonja; Brandl, Katharina; Chu, Huikuan; Jiang, Lu; White, Richard C.; Clarke, Thomas H.; Nguyen, Kevin; Torralba, Manolito; Shao, Yan; Liu, Jinyuan; et al. (Nature (London), 2019)
Chronic liver disease due to alcohol-use disorder contributes markedly to the global burden of disease and mortality 1 – 3 . Alcoholic hepatitis is a severe and life-threatening form of alcohol-associated liver disease. The gut microbiota promotes ethanol-induced liver disease in mice 4 , but little is known about the microbial factors that are responsible for this process. Here we identify cytolysin—a two-subunit exotoxin that is secreted by Enterococcus faecalis 5 , 6 —as a cause of hepatocyte death and liver injury. Compared with non-alcoholic individuals or patients with alcohol-use disorder, patients with alcoholic hepatitis have increased faecal numbers of E. faecalis . The presence of cytolysin-positive (cytolytic) E. faecalis correlated with the severity of liver disease and with mortality in patients with alcoholic hepatitis. Using humanized mice that were colonized with bacteria from the faeces of patients with alcoholic hepatitis, we investigated the therapeutic effects of bacteriophages that target cytolytic E. faecalis . We found that these bacteriophages decrease cytolysin in the liver and abolish ethanol-induced liver disease in humanized mice. Our findings link cytolytic E. faecalis with more severe clinical outcomes and increased mortality in patients with alcoholic hepatitis. We show that bacteriophages can specifically target cytolytic E. faecalis , which provides a method for precisely editing the intestinal microbiota. A clinical trial with a larger cohort is required to validate the relevance of our findings in humans, and to test whether this therapeutic approach is effective for patients with alcoholic hepatitis. In patients with alcoholic hepatitis, cytolysin-positive Enterococcus faecalis strains are correlated with liver disease severity and increased mortality, and in mouse models these strains can be specifically targeted by bacteriophages.